Pengaruh Modal, SIA, Dan Pendapatan Terhadap Nilai Investasi Dengan Harga Saham Sebagai Variabel Moderating - Tetty Tiurma Uli Sipahutar; Citra Pratiwi Sihombing; Febrina Br Manullang; Hantono Hantono (Politeknik Ganesha Medan, 2023)
At the beginning of investment activities, potential investors consider what the desired investment value is, what information is needed, how much capital is needed and other considerations. The purpose of this study was to examine the effect of investment capital, accounting information systems, and income on investment value by using stock prices as a moderating variable. And whether the stock price as a moderating variable, as strengthening the independent and dependent variables, or weakening each variable. The population of this research is himself, who is 200 people taken from the large millennial population aged 17-39 years in the city of Medan. The sample includes 133 millennial respondents from the city of Medan. This data processing technique uses Smart PLS-SEM version 3 software with goodness of fit (internal model), R-squared test, Q-squared test, hypothesis test and t-statistics, resulting in the influence of investment capital, accounting information systems (SIA) has a significant influence on investment value. Income has a large influence on investment value, but share price as a moderator weakens the relationship between investment capital, accounting information systems, and income on investment value, thus rejecting suggestions. To give long-term preparedness or funding options, millennials must be interested in investing their money in the capital market. The results of this study have consequences for the larger community, particularly for the younger generation, who may benefit from it by understanding and becoming more interested in participating in the capital market.